Radio-frequency method for investigation of quantum properties of superconducting structures: Сверхпроводимость и мезоскопические структуры - Il’ichev, E.; Meyer, H.-G.; Krech, W.; Wagner, Th.; Oukhanski, N.; Born, D.; Izmalkov, A.; Grajcar, M.; Smirnov, A.Yu.; Zagoskin, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
We implement the impedance measurement technique (IMT) for characterization of interferometer- type superconducting qubits. In the framework of this method, the interferometer loop is inductively coupled to a high-quality tank circuit. We show that the IMT is a powerful tool to study a response of externally controlled two-level system to different types of excitations. Conclusive information about qubits is obtained from the read-out of the tank properties.